Augmented reality using Appcelerator Titanium Starter : learn to create augmented reality application in no time using the Appcelerator Titanium framework - Ward, Trevor (Packt Pub., 2012)
It's a quick start tutorial to help you get started with creating Augmented Reality applications and acquainting yourself with essential aspects of creating AR applications using the Appcelerator Titanium Framework. The instructions are clear with easy to follow examples. This book is for anybody who wishes to understand how to build an Augmented Reality Application. It uses the Appcelerator Titanium mobile development framework, but the techniques and practices can be applied to other frameworks and native code. You will need to have a good working knowledge of development and JavaScript, it.